2017
DOI: 10.1038/s41598-017-14597-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating different approaches to non-destructive nitrogen status diagnosis of rice using portable RapidSCAN active canopy sensor

Abstract: RapidSCAN is a new portable active crop canopy sensor with three wavebands in red, red-edge, and near infrared spectral regions. The objective of this study was to determine the potential and practical approaches of using this sensor for non-destructive diagnosis of rice nitrogen (N) status. Sixteen plot experiments and ten on-farm experiments were conducted from 2014 to 2016 in Jiansanjiang Experiment Station of the China Agricultural University and Qixing Farm in Northeast China. Two mechanistic and three se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 36 publications
7
53
1
Order By: Relevance
“…More studies are needed to further evaluate this ACS-based PNM strategy in more farmer fields under diverse on-farm conditions. This strategy can be further improved by using three band sensors like Crop Circle ACS 470 or 430 or RapidSCAN, with red edge band [33,65,66] or by incorporating soil and weather information into the algorithm [26,58].…”
Section: Developing Active Sensor-based Precision N Management Strategymentioning
confidence: 99%
“…More studies are needed to further evaluate this ACS-based PNM strategy in more farmer fields under diverse on-farm conditions. This strategy can be further improved by using three band sensors like Crop Circle ACS 470 or 430 or RapidSCAN, with red edge band [33,65,66] or by incorporating soil and weather information into the algorithm [26,58].…”
Section: Developing Active Sensor-based Precision N Management Strategymentioning
confidence: 99%
“…The linear relationships between the single wavelengths derived from CC-470 (R550, R730, and R760) and CC-430 (R670, R730, and R780) at different measurement heights (40,70, and 100 cm) and N status indicators (PNU and NNI) before canopy closure (Feekes 6-7) and after canopy closure (Feekes 9-10) as well as across all the growth stages were established. Consequently, the sensitivities of the single wavelengths of both sensors for estimating N status in winter wheat cultivars were studied (Tables 2).…”
Section: Correlations Between N Status Indicators and Single Wavelengthmentioning
confidence: 99%
“…The linear relationships between the N status indicators (PNU and NNI) and the vegetation indices (NDRE and CI RE ) were derived using CC-470 and CC-430 sensors at three measurement heights (40,70, and 100 cm) and at different crop growth stages (Feekes 6-7, Feekes 9-10, and across all growth stages ( Table 3). The results showed that the values of R 2 for NDRE-PNU and CI RE -PNU relations during the Feekes 6-7 stages at different measurement heights ranged from 0.51 to 0.86 and 0.46 to 0.87 for CC-470, while the corresponding ranges were 0.78-0.86 and 0.79-0.86 for CC-430.…”
Section: Correlations Between N Status Indicators and Vegetation Indicesmentioning
confidence: 99%
“…We are not sure why this difference between studies, but it may be because Yao et al (2014) conducted all their research at a single location, thus resulting in less variation of AGB during the course of their study. Others have looked at the relationship between NDVI and N CONC and have reported both strong ( r 2 = 0.81) and weak ( r 2 = 0.08) correlations (Zhu et al, 2007; Lu et al, 2017), which may be due to differences in rice varieties or the growth stage when data was collected. In other studies, Gnyp et al (2014) examined the relationship between NDVI and AGB and reported the same correlation ( r 2 = 0.51) as our study; while Li et al (2018) examined the relationship between leaf N UP and NDVI and found a similar correlation ( r 2 = 0.70) to our study with plant N UP .…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, there have been relatively few such studies in rice. Some have tested the ability of NDVI to assess rice N status (Zhu et al, 2007; Gnyp et al, 2014; Yao et al, 2014; Lu et al, 2017) and few have used NDVI to develop in‐season yield predictions (Harrell et al, 2011; Yao et al, 2012; Cao et al, 2016). However, most of these studies have focused their research on single sites, leaving at question the scalability of their findings to other sites representing different soils and management practices.…”
mentioning
confidence: 99%